2010
DOI: 10.1590/s0101-31222010000100004
|View full text |Cite
|
Sign up to set email alerts
|

Proteína e qualidade de sementes de feijão (Phaseolus vulgaris L.) em função da adubação nitrogenada em plantio direto

Abstract: eustáquio De sá 3 RESUMO -Além de limitar a produtividade do feijoeiro, a deficiência de nitrogênio pode resultar na produção de sementes com baixo teor de proteína e baixo potencial fisiológico. Nesta pesquisa foram avaliados os efeitos da adubação nitrogenada em cobertura sobre o teor de proteína e o potencial fisiológico de sementes de feijão das cultivares (cv.) IPR Juriti e Pérola, cultivadas em parcelas (solo tipo = Latossolo Vermelho Distrófico), em sistema de plantio direto sob densa palhada de milheto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
1
8
0
3
Order By: Relevance
“…For unfolding N rates within each irrigation management, there were quadratic adjustments to the crude protein content in seeds with the use of Hargreaves-Samani and PenmanMonteith, being the maximum contents obtained with 118 and 77 kg ha -1 N, respectively; however, there was no adjustment of this variable to N rates when using the management by Class A pan. Similar results were obtained by Bordin et al (2003), Gomes Junior et al (2005, Toledo et al (2009) andGomes Junior et al (2010), who found quadratic adjustment of crude protein in response to N topdressing rates, and the maximum contents achieved with rates between 70 and 120 kg ha -1 N. Moreover, these results indicate that different N rates promote increase in the N content in the common bean seeds, resulting in a higher crude protein content. This occurs because the N absorbed by the plant combines itself with carbon skeletons to produce proteins that are broken, translocated and stored in grains in the form of proteins and amino acids (GOMES JUNIOR et al, 2005).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…For unfolding N rates within each irrigation management, there were quadratic adjustments to the crude protein content in seeds with the use of Hargreaves-Samani and PenmanMonteith, being the maximum contents obtained with 118 and 77 kg ha -1 N, respectively; however, there was no adjustment of this variable to N rates when using the management by Class A pan. Similar results were obtained by Bordin et al (2003), Gomes Junior et al (2005, Toledo et al (2009) andGomes Junior et al (2010), who found quadratic adjustment of crude protein in response to N topdressing rates, and the maximum contents achieved with rates between 70 and 120 kg ha -1 N. Moreover, these results indicate that different N rates promote increase in the N content in the common bean seeds, resulting in a higher crude protein content. This occurs because the N absorbed by the plant combines itself with carbon skeletons to produce proteins that are broken, translocated and stored in grains in the form of proteins and amino acids (GOMES JUNIOR et al, 2005).…”
Section: Resultssupporting
confidence: 85%
“…In Brazil, fertilization with nitrogen (N) as topdressing is a practice that has provided increments on the physiological quality and protein content of common bean seeds (BORDIN et al, 2003;GOMES JUNIOR et al, 2005;FARINELLI et al, 2006;TOLEDO et al, 2009;GOMES JUNIOR et al, 2010). The nutrient wich the common bean absorbs the most is N, being necessary for the chlorophyll synthesis as part of this molecule is involved in the photosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…3. The nitrogen concentration in the plant is related to the protein synthesis (TAIZ; ZEIGER, 2013), as verified by Gomes Júnior and Sá (2010) in the bean crop.…”
Section: According Tomentioning
confidence: 88%
“…Nitrogen application resulted in increased soybean seed vigour. Nitrogen applied in the vegetative phase may positively impact seed vigour (Zucareli et al, 2012) as it increases protein contents (Gomes Júnior and Sá, 2010). Some proteins stabilise cell membranes, thereby increasing the physiological performance of the seed (Peske et al, 2012).…”
Section: Effect Of Nitrogen On Physiological Seed Qualitymentioning
confidence: 99%
“…Gomes Júnior and Sá (2010) evaluated the effect of nitrogen application on the physiological quality of bean seeds and observed an increase in crude protein and total soluble protein contents. The reduction of soluble seed protein values negatively affects physiological quality (Gomes Júnior and Sá, 2010). Thus, in general, favourable temperatures and solar radiation, in association with adequate nitrogen fertilisation, facilitates plant growth and improves the physiological quality of the seeds.…”
Section: Effect Of Nitrogen On Physiological Seed Qualitymentioning
confidence: 99%